AGROTOURISM LANDSCAPE PLANNING OF GASOL PERTANIAN ORGANIK COMPANY IN CUGENANG CIANJUR DISTRICT, WEST JAVA - Ardana Reswari, Sotya
In Cianjur, West Java, there is an organic protein powder company named Gasol Pertanian Organik. The company wants to educate people about its organic farming, powder making process, and rare local paddy varieties, so they need to developed the facilities and planning of their agro tourism. The purpose of the final project is to planning restricted alternative tourism area which could educate tourists aboutbthe company, fun, could make tourists taste the local way, and could give benefit for both the company and local communities, while minimalize the disturbance of existing conditions. The method for achieving the result is to research theories, to study about company, to analyze site, to bring out design criteris based on theories and analysis to make big vision, and detailing them through concepts, programs and designs. Besides the main potencies of the site, the supporting potencies are the Sundanese mountainous landscape and culture, while the problems are lack of circulation, a farmers slum settlement, and untreated inorganic waste. The concepts are to restrict visitors and place six thematics zones of agro tourism aea which spread on the company agricultural land. The programs are to purpose authentic activities for visitors that attached to the village, educating and make visitors gain some creative tourism experiences, to improve circulation route based on production plant planting patterns sequence, and to use sustainable utilities systems. The planning must give benefit to both company and local communities.